2015
DOI: 10.3349/ymj.2015.56.5.1338
|View full text |Cite
|
Sign up to set email alerts
|

Focal Lymphocytic Thyroiditis Nodules Share the Features of Papillary Thyroid Cancer on Ultrasound

Abstract: PurposeIt is often difficult to discriminate focal lymphocytic thyroiditis (FLT) or adenomatous hyperplasia (AH) from thyroid cancer if they both have suspicious ultrasound (US) findings. We aimed to make a predictive model of FLT from papillary thyroid cancer (PTC) in suspicious nodules with benign cytologic results.Materials and MethodsWe evaluated 214 patients who had undergone fine-needle aspiration biopsy (FNAB) and had shown thyroid nodules with suspicious US features. PTC was confirmed by surgical patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 28 publications
2
9
0
1
Order By: Relevance
“…It was then observed that absence of calcification is sensitive for diagnosing lymphocytic thyroiditis in the study sample but less specific. Similar finding was observed by Sena hwang et al 10 in their study to differentiate focal lymphocytic thyroiditis from papillary carcinoma Conclusion  Lymphocytic thyroiditis was seen mostly in people with age group30-50.  The mean age of study sample with diagnosis as lymphocytic thyroiditis was 39 years.…”
Section: Discussionsupporting
confidence: 86%
“…It was then observed that absence of calcification is sensitive for diagnosing lymphocytic thyroiditis in the study sample but less specific. Similar finding was observed by Sena hwang et al 10 in their study to differentiate focal lymphocytic thyroiditis from papillary carcinoma Conclusion  Lymphocytic thyroiditis was seen mostly in people with age group30-50.  The mean age of study sample with diagnosis as lymphocytic thyroiditis was 39 years.…”
Section: Discussionsupporting
confidence: 86%
“…1 Embryologically, the thymus migrates from the mandibular angle down to the superior mediastinum, the defects of which may cause the thymus to become ectopically located, either partly or totally, as seen mostly in the cervical region.² Focal lesions of the thyroid gland in children detected by US are mostly benign, rarely malignant thyroid nodules, though focal thyroiditis can be mistaken for thyroid nodules. 3,4 In our study, we depicted thyroid lesions resembling the above mentioned lesions and suggesting thymic tissue due to identical features observed with US. Intrathyroidal ectopic thymus (IET) is rarer than ectopic cervical thymus but more common than believed and frequently detected incidentally on neck US.…”
supporting
confidence: 72%
“…Increased vascularity on color power Doppler is more likely to be seen in focal thyroiditis. 4,16 Yildiz et al 15 found no lesions located in the upper pole of the thyroid gland, ten lesions in the mid portion (91%), and one lesion in the lower pole. In our study, the majority of the lesions were also located in mid portion (n=30, 83%).…”
Section: Discussionmentioning
confidence: 99%
“…yroid nodule disease is common worldwide, and its incidence has grown rapidly over the past decade [1]. With the application of ultrasound (US) technology in thyroid scans, the number of thyroid nodules detected through nonpalpation has increased, reaching 20-67% of the general population [2].…”
Section: Introductionmentioning
confidence: 99%